Designing of english challenge mobile game application as the media of english language learning - Vito Pratama Putra Setyadharma; Emi Iryanti; Indra Hidayatulloh; Novanda Alim Setya Nugraha (Journal of Engineering and Applied Technology, 2020)
English became the first foreign language that came to Indonesia in 1967. The human needs of English can already be seen through lots of official scientific works in English and its intense competitions globally. However, still, many people finds it difficult to learn English, for example, the difficulty in understanding tenses, differences between writing, reading and pronouncing. By relying on the latest features on smartphone, which on the mean time, smartphone is one of many gadgets that is the most practical to use in anywhere and anytime, plus, with gaming contents as the best multimedia entertainer application, learning English will be more interactive and easier to use. In this research, Construct 2 is used as The Developer App and Game Development Life Cycle (GDLC) method of Rido Ramadan and Yani Widyani’s version is used as The Development Method. The game system tested by using black box and by giving out Questionnaire for User Interface Satisfaction to 24 respondents, to test the system’s usability. It resulted 80,83% for the whole of the system,  meaning that the whole system is quiet interesting in the respondents’s view. Then, the screen display gained 80,41%, this means that the screen display is very interesting and did not confuse the respondents. Technology and information game gained 75,41%, this means that the information contained in the game is quiet good, however, further development is needed. The introduction of the game’s system gained 71,63%, means that some of the system’s ability did not run effectively and needed further repairment and development. The last, usability and user interface gained 76,25%, this means that the game is quiet interactive to the respondents.